Public participation in the utilization and rehabilitation of coastal natural resources (case study of coastal erosion in West Kalimantan) - S Ritohardoyo; A A Akbar; J Sartohadi; T S Djohan (Journal of Degraded and Mining Lands Management, 2017)
Emerging development on the coastal region can result in coastal erosion and mangrove ecosystems damage. This disastercould eliminate settlements, agricultural land and public infrastructure. However, for mitigation of those events happened, the government has been constructing the Breakwaters andmangrove reforestation. We used survey method using quota sampling technique in 90 households. The study used a region-based approach. Measurement of socio-economic characteristics, knowledge, perception, and public participation were Chi square test and F test One-Way ANOVA. The results showed that most of samples were middle-lower socio-economy conditions (88.7%). The lower socio-economic caused of 1) the loss of residential and agricultural land due to beach erosion; 2) types of agricultural commodities; 3) work as farmers have the certainty get higher income than as fishermen; and 4) the ability of adaptation in the new location. The high public perception was not accompanied by high levels of public participation to rehabilitate coastal ecosystems